2020
DOI: 10.3389/fcimb.2020.00273
|View full text |Cite
|
Sign up to set email alerts
|

Recent Updates on Outbreaks of Shiga Toxin-Producing Escherichia coli and Its Potential Reservoirs

Abstract: Following infection with certain strains of Shiga toxin-producing Escherichia coli (STEC), particularly enterohemorrhagic ones, patients are at elevated risk for developing life-threatening extraintestinal complications, such as acute renal failure. Hence, these bacteria represent a public health concern in both developed and developing countries. Shiga toxins (Stxs) expressed by STEC are highly cytotoxic class II ribosome-inactivating proteins and primary virulence factors responsible for major clinical signs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
111
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(114 citation statements)
references
References 118 publications
(121 reference statements)
1
111
0
2
Order By: Relevance
“…Even when no significant result was detected for the maintenance of a wide diversity of animal species in a BPS and its association with AM usage, PCA and evidence suggest an important role in the maintenance and transmission of several pathogens, particularly STEC, as all these species have been reported has of STEC and Salmonella spp. reservoirs in Chile and worldwide ( 7 , 11 , 100 , 101 ). In this sense logistic multivariable model highlights the role of within-BPS animal contact increasing the risk of AM usage 9.03 times, perhaps due to an increase in the probability of becoming infected with a pathogen, potentially leading to clinical signs or a decrease in the productive indicators ( 102 ), also it can be related to the presence of several potential host and therefore reservoir for a wide number of pathogens ( 103 , 104 ).…”
Section: Discussionmentioning
confidence: 99%
“…Even when no significant result was detected for the maintenance of a wide diversity of animal species in a BPS and its association with AM usage, PCA and evidence suggest an important role in the maintenance and transmission of several pathogens, particularly STEC, as all these species have been reported has of STEC and Salmonella spp. reservoirs in Chile and worldwide ( 7 , 11 , 100 , 101 ). In this sense logistic multivariable model highlights the role of within-BPS animal contact increasing the risk of AM usage 9.03 times, perhaps due to an increase in the probability of becoming infected with a pathogen, potentially leading to clinical signs or a decrease in the productive indicators ( 102 ), also it can be related to the presence of several potential host and therefore reservoir for a wide number of pathogens ( 103 , 104 ).…”
Section: Discussionmentioning
confidence: 99%
“…STECs have been isolated from a wide variety of domestic and wild animals, while ruminants are recognized as the most important reservoirs of STECs. Human infections are mainly caused by direct contact with infected animals or the consumption of contaminated foods and water [ 16 , 17 ]. As the natural hosts of STECs, cattle, sheep, and pigs are also important repositories for antibiotic resistance genes that potentially impact food and the environment [ 16 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Human infections are mainly caused by direct contact with infected animals or the consumption of contaminated foods and water [ 16 , 17 ]. As the natural hosts of STECs, cattle, sheep, and pigs are also important repositories for antibiotic resistance genes that potentially impact food and the environment [ 16 , 18 ]. For example, the novel plasmid-mediated polymyxin resistance gene, mcr-1 , in zoonotic E. coli was firstly identified in China in November 2015, and was then detected extensively in various Gram-negative bacterial species from domestic animal hosts, as well as animal-originated food around the world [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Shiga toxin-producing Escherichia coli (STEC) is a foodborne human pathogen that causes a wide spectrum of disease varying in severity from asymptomatic carriage, to haemorrhagic colitis, through to life threatening disease such as haemolytic uremic syndrome (HUS) (Paton and Paton, 1998;Castro et al, 2017;Kim et al, 2020). This wide spectrum of disease caused by STEC is due, in part to the immune competence of the individual affected (Karmali et al, 2003), and to the genetic heterogeneity found within STEC strains which involves several virulence factors where their presence/absence or variation within a strain can affect the severity of disease caused by the strain (Bugarel et al, 2011;Haugum et al, 2014).…”
Section: Introductionmentioning
confidence: 99%